2005
DOI: 10.1016/j.mod.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila RYBP gene functions as a Polycomb-dependent transcriptional repressor

Abstract: The Polycomb and trithorax groups of genes control the maintenance of homeotic gene expression in a variety of organisms. A putative participant in the regulation of this process is the murine RYBP (Ring and YY1 Binding Protein) gene. Sequence comparison between different species has identified the homologous gene in Drosophila, the dRYBP gene. We have investigated whether dRYBP participates in the mechanisms of silencing of homeotic genes expression. We first studied its expression by RNA in situ hybridisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 63 publications
4
54
1
1
Order By: Relevance
“…Nub-G4>UAS-dRYBP We have shown that overexpression of dRYBP in wing discs causes the homeotic Ultrabithorax (UBX) protein [24] to be expressed in a limited number of wing disc cells [17,18]. This UBX expression is not dependent on the presence of the NZF domain of the dRYBP protein as overexpression of the dRYBP-DZF and fulllength proteins ( Figure 1L) produced the same pattern of UBX expression in wing discs ( Figure 1O).…”
Section: Nub-g4>uas-drybpmentioning
confidence: 81%
See 4 more Smart Citations
“…Nub-G4>UAS-dRYBP We have shown that overexpression of dRYBP in wing discs causes the homeotic Ultrabithorax (UBX) protein [24] to be expressed in a limited number of wing disc cells [17,18]. This UBX expression is not dependent on the presence of the NZF domain of the dRYBP protein as overexpression of the dRYBP-DZF and fulllength proteins ( Figure 1L) produced the same pattern of UBX expression in wing discs ( Figure 1O).…”
Section: Nub-g4>uas-drybpmentioning
confidence: 81%
“…Using the GAL4/UAS system, we observed that overexpression of the dRYBP protein in wing imaginal discs produces small adult wings [17,18]. We asked whether the reduction of wing size was due to the induction of apoptosis.…”
Section: Exogenous Drybp Expression Induces Apoptotic Cell Deathmentioning
confidence: 99%
See 3 more Smart Citations